Evaluation of molecular primers for sexing the magpie robin and green cucak via CHD1 gene amplification - Fuadah, Khilmi; Rahmawati, Anisa; Fitriana, Fauziah; Aziz, Fatkhanuddin (Fakultas Peternakan Universitas Papua, 2025)
Researchers and breeders are increasingly using the Polymerase Chain Reaction (PCR) method for bird sexing. However, the compatibility of the DNA template and the oligo primer used is the primary key to the success of PCR amplification. In the present study, we evaluated five types of popular PCR primers sexing to determine the sex of a pair of each the magpie robin (Copsychus malabaricus) and green cucak (Chloropsis sonnerati). We used DNA samples from each pair of males and females from the two species above, respectively, to test the five primers listed to amplify the target gene chromodomain helicase DNA binding 1 (CHD1). The results demonstrated that the primer sets of CHD1LF/CHD1LR, CHD1F/CHD1R, and P2/P8 could be used for Copsychus malabaricus, while only CHD1LF/CHD1LR was suitable for Chloropsis sonnerati. It is crucial to select the correct primer to improve bird sexing accuracy because several of the other primers examined in this study were unable to amplify the targeted CHD1 gene correctly.